The art of watercolor lettering : a beginner's step-by-step guide to painting modern calligraphy and lettered art - Klapstein, Kelly (Quarry Books, 2019)
"Learn to letter beautifully with watercolor. In this stunning follow-up to her highly praised and influential first book, The Art of Brush Lettering, lettering expert and workshop instructor Kelly Klapstein (popular on Instagram as @kellycreates) shares her secrets for mastering the essential techniques for creating lovely modern lettering and calligraphy with watercolor. Start with the basics, from choosing paints, brushes, and other supplies to preparing your paper for painting. Learn to handle watercolor paints with essential strokes and warm-ups. Explore painting letterforms in a variety of styles, from traditional to modern. Try a range of creative techniques, including blending ombrés and rainbows, creating pictorial letterforms, and combining watercolor with other mediums. Enhance your lettering with special touches by complementing it with handpainted backgrounds and simple illustrations. With The Art of Watercolor Lettering, you'll learn how to master the medium-and how to go with the watercolor flow-to create one-of-a-kind lettered art and calligraphy that reflect your unique personal style"--